The Influence of Non-planar (Spatial) Links in the Static Characteristics Behavior of Planar Parallel Manipulator - Ganesh Mangavu; Karthikeyan. R; Venkitachalam. P; Guruguhan . G; S. Shrinithi; Kannan. S; Anjan Kumar Dash (IAES International Journal of Robotics and Automation (IJRA), 2017)
Conventional planar manipulators have all their links in a single plane. Increasing payload at the end-effecter/mobile platform can induce high stress in the links due to cantilever nature of links. Thus it limits the total vertical load that can be applied on the mobile platform. In contrast to the links in conventional planar parallel mechanisms, non-planar links are proposed in this paper, i.e., links are made inclined to the horizontal plane and non planar legs are constructed. Although the links are made non-planar, the rotary (or prismatic) joints axes remain perpendicular (or parallel) to the plane of the base platform, which retains the planar motion of the end-effecter. For studying the application of such non planar links in planar manipulators, new models of inertia, stiffness and leg dynamics have to be developed. In this article, these models are developed and with the developed models, the static analysis is done on the planar manipulators with non-planar links and the performance is compared with the corresponding conventional planar manipulators.